Effects of visibility on the modeling of fire evacuation in a multi-storey passenger ship - Ho, Jasmine Bi-Yan. (2009)
Analytical research on evacuation processes carried out in passenger ships has attracted increasing interests over the past few years, with increasing size of the ship. Most of the approaches utilized are flow models. In this paper, an extensive cellular automata (CA) model is proposed to simulate evacuations in a multi-storey passenger ship. CA has been successfully applied to simulate various complex systems, such as those of traffic and fluids. It also provides a more natural approach towards pedestrian dynamics.